Wash basin, Ardeshir Dadysett Pyaav - Ghosh, Ayan (2023)
Ardeshir Dadysett pyaav has taps placed on multiple sides within an ornate niche. Stylistic elements comprise the multifoil arch, fluted pilasters, and floral borders. The wash basin is shaped like a blooming lotus flower.